Type I IFN induces long-chain acyl-CoA synthetase 1 to generate a phosphatidic acid reservoir for lipotoxic saturated fatty acids - Shelley Barnhart; Masami Shimizu-Albergine; Eyal Kedar; Vishal Kothari; Baohai Shao; Melissa Krueger; Cheng-Chieh Hsu; Jingjing Tang; Jenny E. Kanter; Farah Kramer; Danijel Djukovic; Vadim Pascua; et al. (Journal of Lipid Research, 2025)
Long-chain acyl-CoA synthetase 1 (ACSL1) catalyzes the conversion of long-chain fatty acids to acyl-CoAs. ACSL1 is required for β-oxidation in tissues that rely on fatty acids as fuel, but no consensus exists on why ACSL1 is induced by inflammatory mediators in immune cells. We used a comprehensive and unbiased approach to investigate the role of ACSL1 induction by interferon type I (IFN-I) in myeloid cells in vitro and in a mouse model of IFN-I overproduction. Our results show that IFN-I induces ACSL1 in macrophages via its interferon-α/β receptor, and consequently that expression of ACSL1 is increased in myeloid cells from individuals with systemic lupus erythematosus (SLE), an autoimmune condition characterized by increased IFN production. Taking advantage of a myeloid cell-targeted ACSL1-deficient mouse model and a series of lipidomics, proteomics, metabolomics and functional analyses, we show that IFN-I leverages induction of ACSL1 to increase accumulation of fully saturated phosphatidic acid species in macrophages. Conversely, ACSL1 induction is not needed for IFN-I’s ability to induce the prototypical IFN-stimulated protein signature or to suppress proliferation or macrophage metabolism. Loss of ACSL1 in IFN-I stimulated myeloid cells enhances apoptosis and secondary necrosis in vitro, especially in the presence of increased saturated fatty acid load, and in a mouse model of atherosclerosis associated with IFN overproduction, resulting in larger lesion necrotic cores. We propose that ACSL1 induction is a mechanism used by IFN-I to increase phosphatidic acid saturation while protecting the cells from saturated fatty acid-induced cell death.